2017
DOI: 10.1177/0886260517703371
|View full text |Cite
|
Sign up to set email alerts
|

Who Gets Blamed for Rapes: Effects of Immigration Status on the Attribution of Blame Toward Victims and Perpetrators

Abstract: This study examines the influence of the victim's immigration status, perpetrator's immigration status, and participant's immigration status on victim and perpetrator blame attributions. In addition, comparisons between men and women were made. Participants read a rape vignette in the form of a newspaper article and subsequently attributed victim and perpetrator blame. A 2 (victim's immigration status) × 2 (perpetrator's immigration status) × 2 (participant's immigration status) × 2 (gender of participant) bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…The evidence shows that, when the aggression is perceived as the result of certain circumstances related to the perpetrator (e.g., substance use), respondents tend to consider that their interventions are of limited utility (Cinquegrana et al, 2018;Taylor & Sorenson, 2005). Regarding the perpetrator's immigration status, although studies in the field of attitudes toward rape victims have shown the relevance of this variable (Sjöberg & Sarwar, 2017), most studies examining the willingness to report IPVAW scenarios have not specified the immigration status of either victims or perpetrators. To our knowledge, there is only one study that examined the effect of ethnicity in a sample of college students, finding that responses were not influenced by the ethnicity of the perpetrator (West & Wandrei, 2002).…”
Section: Characteristics Of the Ipvaw Episodesmentioning
confidence: 99%
“…The evidence shows that, when the aggression is perceived as the result of certain circumstances related to the perpetrator (e.g., substance use), respondents tend to consider that their interventions are of limited utility (Cinquegrana et al, 2018;Taylor & Sorenson, 2005). Regarding the perpetrator's immigration status, although studies in the field of attitudes toward rape victims have shown the relevance of this variable (Sjöberg & Sarwar, 2017), most studies examining the willingness to report IPVAW scenarios have not specified the immigration status of either victims or perpetrators. To our knowledge, there is only one study that examined the effect of ethnicity in a sample of college students, finding that responses were not influenced by the ethnicity of the perpetrator (West & Wandrei, 2002).…”
Section: Characteristics Of the Ipvaw Episodesmentioning
confidence: 99%
“…Similar to Sjöberg and Sarwar (2020) and Strömwall et al. (2014) , the rape vignette used was presented as a short newspaper article (see the Appendix).…”
Section: Methodsmentioning
confidence: 99%
“…Immigration status was decided based on where the participant’s parents were born. When at least one parent was born outside of Sweden, the participant was deemed to have an immigrant background in line with Sjöberg and Sarwar (2020) , and the historical way immigration status was determined by Statistics Sweden (2002) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Además, la mayor parte de los estudios llevados a cabo en este ámbito se han limitado a analizar las actitudes hacia las víctimas de un delito muy concreto como es la violación. Estos estudios han puesto de relieve la tendencia generalizada a culpabilizar a las víctimas por lo ocurrido (Cameron & Stritzke, 2003;Niemi & Young, 2014Rini, 2015;Sjöberg, & Sarwar, 2017) y han señalado la necesidad de analizar determinados elementos, como el tipo de delitos, las creencias estereotipadas sobre las víctimas o las circunstancias en las que ocurren los hechos, en el estudio de las actitudes hacia las víctimas.…”
Section: Introductionunclassified